The Influence of Price And Product Quality on Consumer Satisfaction With Bottled Drinking Water - Kewo, Stella Theodora; Indrasari, Meithiana (Journal of Innovation in Management, Accounting and Business, 2025)
In today's fast-paced and industrialized world, the issue of price and quality of drinking water has become a major concern for individuals and society. As the demand for safe and reliable water sources continues to increase, the bottled water industry has emerged as a leading player in meeting consumer needs. The study aims to examine and analyze the effect of price on consumer satisfaction of bottled water and to examine the effect of product quality on consumer satisfaction of bottled water. The study was conducted quantitatively, the sampling method was simple random sampling with 170 respondents of Aqua brand mineral water sellers in Gorontalo province. The data that has been collected was then processed using structural equation modeling analysis with a partial least square approach. The results of the study prove that there is a positive effect of price on customer satisfaction, as well as a positive effect of product quality on customer satisfaction of Aqua brand bottled water.